Botanical studies in coastal Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2022)
A report of the botanical studies carried out on the coast of Ecuador is presented, from the first expeditions carried out during the 18th and 19th centuries to the climax of botanical research carried out from the 20th century to the present date. The influence of ocean currents in the formation of bioregions on the coast of Ecuador in mangrove and mainland ecosystems is also discussed, and some morphological trends and taxonomic novelties found in these bioregions are discussed.
Keywords: Diversity; Endemism; Neotropics; Research